ОPEN ACCSESS HERNIOPLASTY IN SUPRAPUBIC INCISIONAL HERNIA - CASE REPORT - Kadri Edjevit; Panikj Katarina; Stosikj Dragan; Dimitrov Zoran (Macedonian Association of Anatomists and Morphologists, 2019)
Introduction: Suprapubic incisional hernia are midline peripheral ventral hernias located within 5 cm of the pubic arch. Most frequently it can occur after gynaecologic surgery procedures. Repair of this type of hernia is still challenging for the surgeons, because it is difficult to fix meshes at the desired position and to achieve adequate overlapping of the defect. This paper will show the case of a patient with suprapubic incisional hernia who has been successfully operated with open access hernioplasty by placing an intraperitoneal composite mesh ( IPOM- intraperitoneal onlay mesh). Case presentation: A 66- year- old female patient, with a history of previous hysterectomy performed with lower midline incision laparotomy and clinically verified suprapubic incisional hernia with the size of a child’s head. CT scan confirmed the incisional hernia defect stretching from the pubic symphysis up to 5 cm below the navel, across all layersof the abdominal wall and it has 2/3 of the small intestine and the sigmoid colon present as a content inside the hernia sac. Open hernia surgical repair was performed and during the operation hernia defect of 9 x 8 cm was measured and according to that an intraperitoneal composite mesh (Parietex- polyester mesh with absorbent collagen film) with dimensions 30 x 20cm was placed. Inferiorly, the mesh was fixed to the Cooper’s ligaments and the pubic bone with non-absorbable tackers. The rest of the mesh was fixed with transfascial sutures through the abdominal muscles. Discussion: After hospital discharge, the patient was followed up during a period of 21 months. In the early postoperative period, postoperative complications such as seroma, hematoma, SSI (surgical site infections), complications related to the mesh (infection, fistula) were not reported. Also, no clinical signs of recurrence were noticed. Conclusion: The decision for the surgical treatment of complex suprapubic hernias is still a challenge for the surgeons. Individual approach leads to successful operative treatment. There is still need of randomized controlled trials to be undertaken, as well as reaching consensus guidelines regarding the ideal method of hernioplasty in the patients with suprapubic incisional hernias.
Keywords: suprapubic incisional hernia (SIH); intraperitoneal composite mesh; IPOM technique